(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The need for data and information about benthic habitat is very necessary to maintain and conserve the ecosystems that exist in the waters. Damage to benthic habitats can occur due to anthropogenic activities and natural disasters that will impact on the surrounding biota and ecosystem, therefore to know and monitor the condition of waters and shallow water habitats it is necessary to do mapping. This study aims to detect the change of ​​benthic habitats in Karang Lebar, Kepulauan Seribu. This study utilized high resolution multispectral imagery QuickBird (2008) and WordView-2 (2018) to detect changes in the distribution and the area of the benthic habitat coverage at the study site. The classification of multispectral imagery was carried out with two approaches, namely the application of the Support Vector Machine (SVM) algorithm and Depth Invariant Index (DII) transformation on both satellite imageries. The number of benthic habitat classes produced was five classes, namely live coral, dead coral, seagrass beds, sand, and rubble. The results of the analysis showed an overall accuracy of 58.18% and 70.9% in the classification with multispectral input bands for the 2008 and 2018 imagery, and 60% and 80% for the DII transformation on 2008 and 2018 imageries respectively. The results of change detection showed the rubble class to sand had the largest area of 81.46 ha.